Comprehensive evaluation of the integrated membrane contactor-microalgae photobioreactor system for simultaneous H2 purification and CO2 treatment from biomass fermented gases - Izzati Izni, Yusoff; Rosiah, Rohani; Nadiah, Khairul Zaman; Rosmawati, Naim; Mohd Sobri, Takriff (Elsevier, 2021)
Biohydrogen (H2) has been identified as a potential renewable energy source to substitute energy-based fossil fuel that can be produced from biomass fermentation. However, carbon dioxide (CO2) is also commonly present in the biogas mixture and must be properly treated as it could contribute to the climate change phenomenon. In this study, an integrated membrane contactor-microalgae photobioreactor system is applied to allow simultaneous H2/CO2 treatment from biomass fermented biogases. A comprehensive evaluation of the effectiveness of the integrated system was investigated by screening the essential operating parameters of the system using One Factor at a Time (OFAT) technique followed by optimization Response Surface Methodology (RSM). Serial investigations of the process parameters, the optimum condition was at a pH of 10 with gas and liquid flow rates at the respective levels of 0.1 L/min and 0.5 L/min, while the microalgae concentration was 0.6 g/L. At these optimum conditions, the H2 purity was found to have increased remarkably, from 69.4% to 83.2%. In a long-term separation performance using the optimized conditions, microalgae solution was found to be capable of sustaining its performance at a longer time with only 2% performance dropped observed within 540 min of the operational time. In conclusion, the use of microalgae in a membrane contactor system could be a promising technique for treating these fermented gases, in a move towards carbon neutrality.